Systemic Expression of Notch Ligand Delta-Like 4 during Mycobacterial Infection Alters the T Cell Immune Response - Schaller, Matthew A.; Allen, Ronald M.; Kimura, Soichiro; Day, Cheryl L.; Kunkel, Steven L. (Frontiers in Immunology, 2016)
The Notch ligand Delta-like 4 (DLL4) is known to fine-tune the CD4+ T cell cytokine response. DLL4 is expressed on the surface of antigen presenting cells in a MyD88 dependent manner. We found that DLL4 expression was upregulated on bone marrow progenitor cells and antigen presenting cells in mice infected with BCG mycobacterium. Transfer of DLL4+ progenitor cells from infected hosts resulted in an increase DLL4+ myeloid cells in the spleen, indicating that expression of the dll4 gene is propagated throughout hematopoiesis. We also found an increase in DLL4+ monocytes from individuals that were infected with M. tuberculosis. In latent individuals, DLL4 expression correlated with increased cytokine production from T cells in response to PPD stimulation. Finally, antibody blockade of DLL4 reduced T cell cytokine production from naïve T cells stimulated with antigen. These results demonstrate that the Notch ligand DLL4 can influence T cell cytokine production in both humans and mice, and further reveal that expression of DLL4 is upregulated on early hematopoietic progenitors in response to chronic mycobacterial infection. These data suggest that widespread DLL4 expression may occur as a result of mycobacterial infection, and that this expression may alter CD4+ T cell responses to both previously encountered and novel antigens.